Banking Crises under a Central Bank Digital Currency (CBDC) - Lea Bitter (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
One of the main concerns associated with central bank digital currencies (CBDC) is the disintermediating effect on the banking sector in general, and the risk of bank runs in times of crisis in particular. This paper examines the implications of an interest-bearing CBDC on banking crises in a dynamic bank run model with a financial accelerator. The analysis distinguishes between bank failures due to illiquidity and due to insolvency. In a numerical exercise, CBDC leads to a reduction in the net worth of banks in normal times but mitigates the risk of a bank run in times of crisis. The financial stability implications also depend on how CBDC is accounted for on the asset side of the central bank balance sheet: if CBDC issuance is offset by asset purchases, it delays the onset of both types of bank failures to larger shocks. In contrast, if CBDC issuance is offset by loans to banks, it substantially impedes failures due to illiquidity, but only marginally affects bank failures due to insolvency.
Keywords: E42; E58; G01; G21; 330; central bank digital currency; financial intermediation; financial stability; bank runs